Airflow Performance in Close Sided Vertical Channel - Ahmed Habeb (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
This paper reports on a natural convection experimental study conducted on a vertical test rig measuring 10 cm in height and 10 cm in width. The project was designed to collect temperatures and airflow velocities under different operating conditions, various channel depths and different heat inputs in order to obtain additional parameters required for analysis. The purpose and the main target of the project are to provide a clear picture of the flow behavior in this type of application. Extensive analysis was carried out to evaluate airflow rate, heat transfer coefficient and other related parameters. It was found that Nusselt number (Nu) is a function of the modified Rayleigh number (Ra*) and the aspect ratio (s/H). In addition, the Reynolds number Re(s) is a function of (Ra*) and (s/H). Dimensionless correlations between Nu, Re and Ra* were derived. Moreover, previous theoretical studies suggested that the flow rate should be proportional to the cube root of the heat input, while earlier experimental results indicate a higher exponent. However, the current experimental results suggest a value in between; the flow rate is demonstrated to be dependent on the aspect ratio, with a proportionality of approximately 0.66.